Influence of sinter-cooling rate on intergranular corrosion of powder metallurgy superaustenitic stainless steel. (October 2014) - Martin, F.; García, C.; Blanco, Y.; Herranz, G.
Abstract : Powder metallurgy superaustenitic stainless steel sintered in N2 –H2 atmosphere (95%–5%) was obtained. Three different processes were applied by controlling the sinter-cooling rate (furnace, gas and water). Intergranular corrosion resistance was evaluated. Furthermore, microstructure, density, porosity, macro- and microhardness were investigated. Microstructures were characterised by optical microscopy and scanning electron microscopy with energy dispersive analysis of X-rays. Intergranular corrosion behaviour was evaluated by immersion and by single and double loop electrochemical potentio-kinetic reactivation tests. The superaustenitic steel after fast cooling by water quenching showed the best intergranular corrosion behaviour, the highest microhardness values and the most homogeneous microstructure.